Forensic Medicine Curriculum in Medical Schools of Malaysia- A review (Bangladesh Journal of Medical Education, 2017)
Every medical graduate has to compulsorily serve the government in Malaysia, before he can be a duly registered medical practitioner with the Malaysian Medical Council, in order to practise within Malaysia. During the course of his service as a Government Medical Officer, he is required to undertake medico-legal examinations of living and medico-legal autopsy of the dead relating to common offences, etc. These medical examinations are required by law for dispensing justice, as per the Penal Code, and other laws common to Malaysia and other former British Colonial countries of south Asian region. However the undergraduate Forensic Medicine curriculum has been progressively whittled down through repeated amendments of the undergraduate syllabus on the lines followed in some of the more developed nations. The latter have adequate post-graduate qualified Forensic experts in each district to undertake these tasks, and do not require the medical graduate to undertake these onerous and difficult examinations in their districts. This reduction of the under-graduate Forensic syllabus has resulted in many of the graduates not being given exposure to the minimal content necessary to undertake these examinations. They are thus uninitiated and unaware of the various situations and their responsibilities where they may be required to undertake these examinations for corroborating a crime or proving the innocence of a suspect examined. This paper lays emphasis on the legal expectations and also about standardization of forensic medicine curriculum for undergraduate medical degrees in Malaysian medical schools.Bangladesh Journal of Medical Education Vol.5(1) 2014: 2-5